BUDAYA KERJA PEGAWAI PADA BAGIAN ORGANISASI SEKRETARIAT PEMERINTAH DAERAH KABUPATEN DONGGALA - Purnamasari, Dian (Katalogis, 2015)
This research aims at describing employee work culture ini regional secretariat organization of Donggala Regency. The method used in this research is descriptive qualitative. The data were collected through observation, interview, and documentation. There were 5 informant that selected purposively. Approach used ini this research is work culture from Stefans P. Robbins cuvering: discipline, openness, respect, coorporation. The result of this research shows that employee work culture has not productive yet. The result of this research shows that there are some aspects influence the employee’s work cultures, such as: less discipline to the procedure and time. However, the ability of sharing and receiving information, between work partner is good, respect to each othe, respect to their own duty, and responsibility among partner, cooperation in sharing and receiving help are already good as well.